Self Efficacy, Partisipasi Anggaran, Asimetri Informasi, Emosional Stability dan Penekanan Anggaran terhadap Senjangan Anggaran - Ardianti, Putu Novia Hapsari; Damayanti, Ni Nyoman Sri Rahayu; Prayoga, I Made Surya (E-Jurnal Akuntansi; Vol 31 No 2 (2021), 2021)
A budget is an organizational plan stated in a monetary unit and drawn up for a period of time. The process of budgeting can trigger the behavior of budget implementers to conduct budgetary slack due to negative subjective attitudes and norms owned by budget executives. This makes research on the factors that affect the budgeting slack important to be carried out. This study used data collection techniques with questionnaires. All research instruments are valid and reliable. This research has also been freed from the problem of classical assumptions. The results were tested with multiple linear regression analysis. The results showed self-efficacy, budget participation, information asymmetry, and budgetary emphasis influenced the budgetary slack. On the other side emotional stability has no significant effect on the budgetary slack. Keywords: Self-efficacy; Budget Participation; Information Asymmetry; Emotional stability; Budgetary Emphasis; Budgetary Slack.